Der neue Finanzausgleich zwischen Bund und Ländern: erste Ergebnisse und Bewertungen; The new federal fiscal equalisation system 2020: First results and evaluation - André W. Heinemann (Wirtschaftsdienst, 2021)
Bereits 2015 wurde erstmalig durch die Konferenz der Ministerpräsident:innen ein neues Finanzausgleichssystem ab 2020 diskutiert und beschlossen. Seitdem sind zahlreiche Beiträge zu den möglichen fiskalischen Auswirkungen, Anreizproblematiken und Bewertungen einiger Detailregelungen entstanden und debattiert worden. Nach der ersten Durchführung im Ausgleichsjahr 2020 ist es nun Zeit, erstmalig auf konkrete Ergebnisse einzugehen und dabei verbliebene und neue Probleme offen zu diskutieren. – – The new Federal Fiscal Equalization System became effective on 1 January, 2020. While all public budgets in the federal system of Germany were faced with high decreases in revenues caused by the measures to fight the impacts of the COVID-19 pandemic in 2020, a first evaluation shows that the differences to the old system are rather marginal. The focus now lies on the vertical distribution of the value-added tax, whereas for the fiscal capacity equalisation only revenue of the Laender are used as before. In fact, the supplementary federal grants, the federal grants for special needs and very critical new federal grants are still problematic and a strong signal for centralisation.
Keywords: H24; H22; D31; 330; Finanzausgleich; Deutschland